Epiphanies and learning in a postcolonial Malaysian context : A preliminary evaluation of international social work placements - Dolly, Paul Carlo; Crabtree, Sara Ashencaen; Parker, Jonathan; Azinda, Azman (SAGE Publications Ltd., 2014)
This article discusses preliminary findings from a study of international placement learning of British social work students in social welfare settings in Malaysia. Research data generated focuses on the learning processes experienced by the students placed in an unfamiliar, postcolonial context with an emphasis on issues relating to diversity and developing critical cultural competence. Future sustainability and benefits of such placements are also reviewed.